FROM THE FRINGES TO THE FOREFRONT: THE RISE OF THE BHARATIYA JANATA PARTY (BJP) IN NAGALAND - Jangmei, Riamei (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper delves into the intriguing phenomenon of the Bharatiya Janata Party’s (BJP) rise to prominence in Nagaland, a state with a predominantly Christian population. Historically, Nagaland’s political landscape has been dominated by regional parties advocating for distinct ethnic and tribal interests. However, the BJP’s recent electoral successes have significantly challenged this established political order, prompting inquiries into the factors driving its rise.